VAKSINASI, EDUKASI DAN ELIMINASI ANJING LIAR SEBAGAI USAHA PERCEPATAN PENANGGULANGAN PENYAKIT RABIES DI BALI - INK, Kerta Besung.; Suwiti, NK.; Suatha, IK.; Suastika, P.; Piraksa, IW.; Setiasih, NL. Eka (Buletin Udayana Mengabdi; Vol 10 No 2 (2011): Jurnal Udayana Mengabdi, 2012)
Rabies is an old zoonotic disease coused by lyssavirus of Rhabdovirus family, affecting warm-blooded animal including human. This community service is required to give information about the rabies diseases, vaccination and elimination of stray dogs. This activities was cooperated with Department of Animal Husbandry in Denpasar, Badung, Gianyar and Tabanan regency. The method used in this activities were to give information about the rabies diseases, to give vaccination and elimination of stray dogs. The number of dog vaccinated is: 172, eliminated : 81, and the activity was attended by 348 people, all of them were interested in this program. This activity should be continued, because when the rabies disease outbursts, it is very difficult to eradicate.